Ремоделювання яєчників щурів за умов уведення розчинів важких металів - Колосова, Ірина; Kolosova, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
Вплив низьких доз ацетату свинцю призводив до зменшення кількості примордіальних фолікулів при збільшенні атретичних, передчасного регресу жовтих тіл. За поєднаного введення ацетату свинцю й цитрату срібла кількісний склад основних компонентів яєчників – фолікулів і жовтих тіл – наближено до показників норми. Experimentally we investigated the changes of the main structural elements of the ovaries in conditions of isolated administration of low doses of lead acetate and combined with silver citrate prepared using aquananotechnology. Rats were divided into three groups: an experimental group №1 – animals that received lead acetate at a dose of 0.05 mg / kg, n = 8; experimental group № 2 –animals that received lead acetate at a dose of 0.05 mg / kg with a solution of silver citrate in a dose of 2 mcg / kg, n = 8; group № 3 – control, animals that received distilled water, n = 8 each group, pregnant females are divided depending on the stage on which the planned and ovaries fruit extract for further research into 3 groups: females with gestation 12, 16 and 20 days. Analysis of the results showed that the introduction of insulated lead acetate lead to a decrease in the number of primordial follicles by increasing atresial, premature regression of corpora lutea. As result of the combined effects of lead acetate solution to the silver citrate were observed increase in the number of corpora lutea and primordial follicles with decreasing atresial that testifies to decrease the negative effect of lead acetate on morphological and functional condition of the ovaries of rats in the experiment.
Remodeling of the Ovaries of the Rats by the Infusion of Heavy Metals.
Keywords: ацетат свинцю; жовті тіла; фолікули; яєчники; репродуктивна система; lead acetate; corpora lutea; follicles; ovaries; reproductive system